Improvement of Soil Properties through Farmyard Manure and Lime for Barley Productivity in Acidic Hot Spot Areas of Ethiopia - Addis, Zelalem; Amare, Tadele; Keribih, Betewlegn; Getaneh, Desaleign; Ambaw, Zimie; Awoke, Abrham; Tenaegn, Abere (Department of Agronomy and Horticulture, IPB University, 2025)
The experiment was conducted to enhance barley productivity and improve soil properties in acid hotspots areas by applying farmyard manure and varying lime rates in the northwestern Amhara region, Ethiopia. The experiment comprised the combination of three levels of farmyard manure (0, 2, and 4 t.ha-1) and four levels of lime (0, 25, 50, and 100%) with one plot containing 92% N from urea and 69% P2O5 from TSP which was laid out in randomized complete block design with three replications. Data on soil physico-chemical properties and yield components of barley were collected and subjected to ANOVA. The individual application of farmyard manure and lime had a significant impact on the yield components of barley. Similarly, soil properties changed slightly under the treatments compared to the soil before planting. Sole application of 4 t.ha-1 farmyard manure and 100% lime ( 8.8 t.ha-1) gives the highest grain and above-ground biomass yield (1.7 and 3.5 t.ha-1) and (1.6 and 3.1 t.ha-1), respectively, than the control and the pilot treatments. Similarly, the application of sole 4 t.ha-1 scored the highest plant height (72.9 cm) compared to the control and pilot treatments. To achieve the highest net benefit within a short period, applying 4 t.ha-1 and 25% (2.2 t.ha-1) can be preferable for yield improvement in the study area and similar agro-ecological environments.